Molecular characterization of multidrug resistant pseudomonas aeruginosa / Abdelkodose Mohammed Hussen Abdulla - Hussen Abdulla, Abdelkodose Mohammed (2012)

(untitled)
Pseudomonas aeruginosa is one of the main causes of healthcare-associated infections among hospitalized patients. Healthcare-associated infections predominantly lead to pneumonia, urinary tract infections, as well as skin and soft-tissue infections. This organism is commonly multiresistant and leads to morbidity and mortality. In this study, the resistance mechanisms of 88 clinical P. aeruginosa isolates from the Department of Medical Microbiology, Faculty of Medicine, University of Malaya, Kuala Lumpur, Malaysia were evaluated. The antibiotics resistance profiles of these isolates were determined and this was followed by evaluating the expression levels of AmpC cephalosporinase, the multidrug efflux pumps, the OprD outer membrane porin and the penicillin binding protein (PBP2, PBP3). Selected clinical isolates that were resistant to imipenem and meropenem were evaluated for metallo--lactamase (MBL) and extended spectrum β-lactamases (ESBL) production. The antimicrobial agents tested in this work were piperacillin/tazobactam, ceftazidime, aztreonam, amikacin, gentamicin, ciprofloxacin, imipenem, meropenem and colistin. These agents were selected as representatives of the primary antibiotic classes used to treat P. aeruginosa infections. The clinical specimens of P. aeruginosa isolates were isolated from urine (53.4%), wound (21.6 %), sputum (5.7%), blood (5.7%) and in dwelling medical devices (13.6 %) as shown in Table 3.1a. Samples were collected from patients hospitalized in the surgical (31), medical (20), orthopedic (13), paediatric (7), neurosurgery (7), intensive care unit (ICU) (5), otorhinolaryngology (ENT) (3) and gynaecology wards (2). Of these isolates, 47 were from urine, 19 from wounds, 12 from in dwelling medical devices, 5 from blood, and 5 from sputum. iv In the isolates tested. The highest resistance was observed for gentamicin (94.0%), ciprofloxacin and ceftazidime (92%), imipenem (74.0%), meropenem (78%), amikacin (66.0%), piperacillin/tazobactam (58.0%), aztreonam (56.0%) and colistin (7.0%), with the surgical department having the highest of numbers of isolates resistant for all antibiotics except colistin with urine and wound specimens being most resistant to the antibiotics except for colistin. The gene expression analysis of 88 P. aeruginosa isolates showed overexpression of efflux pump genes for MexY (82.0%, from 2.0 to 1731.0 fold), MexB (73.0%, from 2.0 to 50.0 fold), MexEF (68.0%, from 2.9 to 371), MexZ (66.0%) and MexCD (48.0%, from 2.0 to 522), while for AmpC overexpression it was 65.0% (from 10.4 to 1806.0 fold). Down regulation were noted for OprD (97.0%, from 0.2 to 0.7 fold), PBP2 (77.0%, from 0.1 to 0.7 fold), PBP3 (84.0%, from 0.01 to 0.7 fold) and OprM (65%, from 0.2 to 0.7) as compared to those of P. aeruginosa ATCC 27853. Among the resistant isolates overexpressed for the MexB and MexY efflux gene, the lowest mRNA expression was noted for isolates resistant to colistin, whereas the highest mRNA expression was noted for isolates resistant to ciprofloxacin and amikacin respectively. For the overexpression of MexCD and MexEF genes, the lowest mRNA expression was seen with isolates resistant to piperacillin/tazobactam. However, the highest overexpression for MexCD was seen with isolates resistant to meropenem and aztreonam while the highest overexpression for MexEF gene was noted with isolates resistant to colistin. For the overexpression of AmpC gene, the lowest mRNA expression was seen with isolates resistant to colistin and the highest mRNA expression was noted with isolates resistant to piperacillin/tazobactam. All isolates resistant to meropenem, imipenem and colistin demonstrated lower mRNA expression for OprD gene while as for OprM gene, the lowest v mRNA expression was observed in isolates resistant to amikacin. For the PBP gene, isolates resistant to colistin had lower mRNA expression for PBP2, PBP3 while those resistant to imipenem had higher mRNA expression. With regard to the significance of the above results, the overexpressions of MexY gene were significantly different in isolates resistant to amikacin, gentamicin and ciprofloxacin as compared to other antibiotics (p < 0.05), while, for the AmpC gene, mRNA expression in P. aeruginosa isolates demonstrated high significant differences towards piperacillin/tazobactam antibiotics as compared to other antibiotics (p < 0.05). Sixty-five of the clinical P. aeruginosa isolates that were resistant to imipenem and meropenem were then evaluated for detection of 6 different metallo-beta-lactamase (MBL) genes (blaIMP, blaVIM, blaGIM, blaSIM, blaSPM and blaNDM). In addition, these isolates were tested for the extended spectrum beta-lactamase (ESBL) production genes (blaVEB, blaTEM, blaCTX-M, blaSHV and blaPER) using PCR. Among the 65 imipenem and meropenem resistant, 41 isolates were metallo-β-lactamase (MBL) producers and these genes blaIMP, blaVIM, blaGIM, blaNDM and blaSIM were detected in 20, 14, 4, 2, and in 1 isolates respectively. Thirty-three of these 65 isolates tested positive for 3 ESBL genes out of which PCR positive isolates were present in 25 isolates for the blaVEB gene, 5 isolates for the blaTEM gene and 3 isolates for the blaCTX-M gene respectively. Most of the P. aeruginosa clinical isolates had a high level of resistance to examined antibiotics except colistin. Multidrug resistance phenotype in these clinical isolates was caused by the interaction of several different resistance mechanisms occurring within the same strain such as overexpression of efflux, AmpC overproduction or decreased outer membrane porin OprD, alteration of penicillin binding protein. Additionally, these strains highlight the ability of P. aeruginosa to develop dual resistance to different classes vi of antimicrobial agents through independent mechanisms of resistance and highlight the need for the judicious use of therapy when dealing with P. aeruginosa to prevent multidrug resistance. The clinical P. aeruginosa isolates that were resistant to imipenem and meropenem demonstrated high efflux overproduction, MBL and ESBL production that confirm these resistance genes has the ability to increase the resistance to imipenem and meropenem among P. aeruginosa.